Engineering Design Process of Mobile Back Cover - Sachin Chavan; R.S. Lavate; M.K. Beldar; Avishi Saini (International Journal of Industrial and Product Design Engineering, 2024)
A mobile back cover protects phone from dents and scratches if anyone accidentally drop it. Most importantly, they enable a good grip on the phone. Cases, which are designed to attach to, support, or otherwise hold a Smartphone, are popular accessories for a mobile phone. Mobile back case measures are based on the display inches (e.g. 5 inch display). Many other different types are Pouches and sleeves, holsters, shells, fitted cases, flip cases and wallets, screen protection and body films, Drop and shock protection, Leather case and Cases with integrated kick stands. Mobile covers can also personalize as per customer’s needs. These are the result of the relatively "naked" designs produced by manufacturers such as Apple, where the metal and glass components of the device are exposed and vulnerable to damage. This research paper mainly deals with a detailed and in-depth study of mobile back cover from a manufacturer’s point of view such that the problems related to the cover are effectively minimized and can satisfy consumers requirements and desires
Keywords: Mobile back cover; Product architecture; aesthetic; concept generation; design for environment; design for manufacturing; ergonomics; market survey; modular; product life cycle; quality functional deployment